1997
DOI: 10.1074/jbc.272.43.26833
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Extends the Lifetime of the Activated Insulin Receptor Complex in Endosomes

Abstract: Insulin signal transduction, initiated by binding of insulin to its receptor at the plasma membrane, activates the intrinsic receptor tyrosine kinase and leads to internalization of the activated ligand-receptor complex into endosomes. This study addresses the role played by the activated insulin receptor within hepatic endosomes and provides evidence for its central role in insulinstimulated events in vivo. Rats were treated with chloroquine, an acidotrophic agent that has been shown previously to inhibit end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 55 publications
(62 reference statements)
4
35
0
Order By: Relevance
“…In addition, similarly to what is occurring in cells expressing IR R252C , IRS 1 phosphorylation could be achieved by IR C860S localised mainly on microvilli supporting the idea that some IR biological signals can be elicited from these surface domains. However, endosome could also be a site of IR signal transduction and biological responsiveness, as suggested by studies of the kinetics of IR kinase activation and of the subcellular localisation of this kinase domain [18,19,20,42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similarly to what is occurring in cells expressing IR R252C , IRS 1 phosphorylation could be achieved by IR C860S localised mainly on microvilli supporting the idea that some IR biological signals can be elicited from these surface domains. However, endosome could also be a site of IR signal transduction and biological responsiveness, as suggested by studies of the kinetics of IR kinase activation and of the subcellular localisation of this kinase domain [18,19,20,42].…”
Section: Discussionmentioning
confidence: 99%
“…In previous work we showed that inhibition of endosomal acidification with chloroquine inhibited both insulin degradation and dissociation of insulin-IRK complexes within endosomes (18), with the consequent augmentation of IRK activity in this compartment (19). Because a critical role for endosomal IRK in insulin signaling has been clearly demonstrated (5), it was postulated that the inhibition of vacuolar acidification might potentiate insulin signaling from endosomes (19).…”
Section: Figmentioning
confidence: 99%
“…This suggests that inhibitors of vacuolar acidification would potentiate insulin signaling from the endosomal compartment, and there are studies consistent with this view. Thus, in rats, chloroquine treatment augmented and prolonged IRK activity in hepatic endosomes (19). Further, the administration of chloroquine to patients with type 2 diabetes mellitus decreased fasting plasma glucose levels, improved glucose tolerance, and increased plasma insulin levels (20 -22).…”
mentioning
confidence: 99%
“…4), because all the three inhibitors are thought to work inside the cells. Chloroquine is thought to inhibit proteolysis at the late stage of endosomes (5,20,34), probably due to inhibition of acidification of endosomes. MG-132 is an inhibitor of proteasomes (20,32) that is thought to degrade the ubiquitinated EGF receptor downstream of the endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we examined the participation of this pathway by interfering with it. The cells were pretreated with MDC, an inhibitor of clathrin-dependent endocytosis (13), chloroquine, an inhibitor of endosomal proteolysis (5,20,34), MG-132, a proteasome inhibitor (20,32), or herbimycin A, a tyrosine kinase inhibitor, in media containing EGF (10 ng/ml) but no serum. In untreated cells, which were not treated with any of the inhibitors, the relative intensity of the EGF receptor increased 1.2-fold on average at 2 min after shaking for 5 min.…”
Section: Increase In Egf Receptor Induced By Shaking Does Not Involvementioning
confidence: 99%